Psychological Peculiarities of Teachers with Different Levels of Altruism - Ostrovska, Kateryna (Psychological Prospects Journal, 2015)
Personal indices of correctional teachers and school teachers have been compared in the research. According to the results of a comparison the following conclusions were made: 1) a group of correctional teachers has higher level of altruistic orientation; 2) in a group of correctional teachers prevailing focus is on practice, while school teachers are focused on communication; 3) correctional teachers are more focused on work and its result, on altruism and a dominant position in their environment. On the contrary, the teachers of secondary schools are focused on the process of activity, obtaining wealth, selfishness that leads to freedom; 4) the methods of teachers achieving their life goals have been defined. So teachers of secondary schools achieve self-confidence when they feel sufficiently educated. A priority way to achieve their goals is the knowledge and communication. Correctional teachers choose tolerance as their strategy. Through compassionate attitude towards others, their altruism, altruistic willingness, romantic works, sometimes even associated with danger, they get a commitment of environment, acknowledgement. Later in practice they use altruism to achieve dominance, power, which is based on acquired authority of work during long period for the desired result – correction of developmental abnormalities of a student. According to a comparative analysis of the Scheffe criteria it was found that correctional teachers with an average level of altruism have higher level of patience, sensitivity and direction for the work than the teachers with high and low levels of altruism.